2020
DOI: 10.1038/s41598-020-76140-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of secoiridoid glycosides in leaves of UK and Danish ash provide new insight for ash dieback management

Abstract: Secoiridoid glycosides are anti-feeding deterrents of the Oleaceae family recently highlighted as potential biomarkers in Danish ash trees to differentiate between those tolerant and susceptible to the fungal disease ash dieback. With the knowledge that emerald ash borer has recently entered Europe from Russia, and that extensive selection trials are ongoing in Europe for ash dieback tolerant European ash (Fraxinus excelsior), we undertook comprehensive screening of secoiridoid glycosides in leaf extracts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…There is no set recommended dosage for oleuropein intake per day but many studies have shown that olive leaf extract (containing approximately 20% oleuropein) at the dose of 1,000 mg/day depicted no observed adverse side effects (Breakspear & Guillaume, 2020; Clewell et al., 2016). OL is not solely a component of Olea genus, it also occurs in several other genera of Oleaceae family such as Fraxinus chinensis (Chang et al., 2020), F. angustifolia (Kasmi et al., 2021), F. excelsior (Sidda et al., 2020), Syringa vulgaris (Hanganu et al., 2021), S. josikaea (Damtoft et al., 1993), Ligustrum vulgare (Macková et al., 2013), L. ovalifolium (Hosny et al., 2009), and Philyrea latifolia (Tattini et al., 2000). Table 1 represents the oleuropein content in different parts/products of olive tree.…”
Section: Occurrence Chemistry and Biosynthesis Of Oleuropeinmentioning
confidence: 99%
“…There is no set recommended dosage for oleuropein intake per day but many studies have shown that olive leaf extract (containing approximately 20% oleuropein) at the dose of 1,000 mg/day depicted no observed adverse side effects (Breakspear & Guillaume, 2020; Clewell et al., 2016). OL is not solely a component of Olea genus, it also occurs in several other genera of Oleaceae family such as Fraxinus chinensis (Chang et al., 2020), F. angustifolia (Kasmi et al., 2021), F. excelsior (Sidda et al., 2020), Syringa vulgaris (Hanganu et al., 2021), S. josikaea (Damtoft et al., 1993), Ligustrum vulgare (Macková et al., 2013), L. ovalifolium (Hosny et al., 2009), and Philyrea latifolia (Tattini et al., 2000). Table 1 represents the oleuropein content in different parts/products of olive tree.…”
Section: Occurrence Chemistry and Biosynthesis Of Oleuropeinmentioning
confidence: 99%
“…2781 ) and GL5 ( m/z 928 . 3429 ), found in higher concentrations in trees that are highly susceptible to ash dieback in previous investigations (39, 49), were significantly higher in low larval kill individuals compared to uninfested individuals across families. Additionally, we found that concentrations of verbascoside, a phenylethanoid glycoside also proposed as a component of the resistance response (36), were highest in low larval kill individuals.…”
Section: Resultsmentioning
confidence: 55%
“…One secoiridoid (m/z 569.23) was elevated in all infested comparisons (LLK v UNI, HLK v UNI) across all families, and may have some value as an indicator of infestation across many ash genotypes. Another two secoiridoids, nueznehide (m/z 704.2781) and GL5 (m/z 928.3429), found in higher concentrations in trees that are highly susceptible to ash dieback in previous investigations (39,49), were significantly higher in low larval kill individuals compared to uninfested individuals across families. Additionally, we found that concentrations of verbascoside, a phenylethanoid glycoside also proposed as a component of the resistance response (36), were highest in low larval kill individuals.…”
Section: Metabolite Based Opls-da Models Correctly Identify Progeny C...mentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, compounds 81 with m/z 601 and molecular formula C 27 H 38 O 15 was tentatively identified as frameroside or 2″-epi-frameroside; Sidda and co-workers [ 39 ] identified them in ash leaves from Oleaceae family.…”
Section: Resultsmentioning
confidence: 99%